GAMBARAN HARGA DIRI PASIEN THALASEMIA REMAJA (usia 14-21 tahun) DI KLINIK HEMATO-ONKOLOGI RSUP Dr. HASAN SADIKIN BANDUNG - Maghfiroh, Riska; Okatiranti, Okatiranti; Sitorus, Ria E (KEPERAWATAN, 2014)
Abstract - Thalassemia is a group of hereditary diseases or conditions in which the production of one or more than one type of polypeptide chain is characterized by impaired hemoglobin levels decreased. In January 2013 recorded 230 thalassemia patients hemato-oncology clinicsÂ  and 70% are adolescent thalassemia patients aged 14-21 years. Thalassemia impact physical changes such as mongoloid face, body growth is less than perfect, enlarged liver and spleen that can affect the self-esteem of patients. Self-esteem is a self-assessment that reflects the attitude of acceptance or rejection, and show how far the individual believes that he is capable, important, successful and valuable. Research purposes to describe the adolescent self-thalassemia patients (aged 14-21 years) in hemato-oncology ClinicÂ  with descriptive research. The sampling technique used is purposive sampling with a sample of adolescent thalassemia patients (aged 14-21 years) with a sample of 41 respondents. Adolescent self-esteem was measured using the Coopersmith self-esteem scale. Assessment criteria using the mean, which if mean <15.2 is categorized low self-esteem, whereas if the mean of â¥ 15.2 were categorized high esteem. The results showed 46.3% of low self esteem and high self-esteem 53.7%. At felling of belongin 58.5% assessed with high self-esteem, felling of competence 61% assessed with low self-esteem, felling of worth 51.6% assessed with high self-esteem , of the three components of self-esteem only the assessed components capable of feeling so low that it can be concluded adolescent thalassemia patients have high self-esteem.This needs to be maintained and to improve the lower component, should the effort of health workers to help patients identify positive aspects and capabilities.Â Keywords: Thalassemia, self-esteem, adolescentÂ Abstrak - Thalasemia adalah sekelompok penyakit atauÂ  keadaan herediter dimana produksi satu atau lebih dari satu jenis rantai polipeptida terganggu yang dikarakteristikkan dengan penurunan kadar Hb. Pada bulan Januari 2013 tercatat 230 pasien thalasemia Kinik Hemato-OnkologiÂ  dan 70% nya adalah pasien thalasemia remaja usia 14-21 tahun. Thalasemia memberikan dampak perubahan fisik seperti muka mongoloid, pertumbuhan badan kurang sempurna, pembesaran hati dan limpa yang dapat mempengaruhi harga diri pasien. Harga diri adalah suatu penilaian terhadap diri sendiri yang mencerminkan sikap penerimaan atau penolakan dan menunjukkan seberapa jauh individu percaya bahwa dirinya mampu, penting, berhasil dan berharga. Tujuan penelitian untuk mengetahui gambaran harga diri pasien thalasemia remaja (usia 14-21 tahun) di Klinik Hemato-OnkologiÂ  dengan jenis penelitian deskriptif. Teknik sampling yang digunakan adalah purposive sampling dengan sampel pasien thalasemia remaja (usia 14-21 tahun) dengan jumlah sampel 41 responden. Harga diri remaja diukur dengan menggunakan skala harga diri Coopersmith. Kriteria penilaian menggunakan mean, dimana jika mean < 15.2 dikategorikan harga diri rendah, sedangkan jika mean â¥ 15.2 dikategorikan harga diri tinggi.Hasil penelitian menunjukkan 46.3% harga diri rendah dan 53.7% harga diri tinggi. Pada komponen perasaan diterima (felling of belongin) 58.5% dinilai dengan harga diri tinggi, pada komponen perasaan mampu (felling of competence) 61 % dinilai dengan harga diri rendah, pada komponen perasaan berharga (felling of worth) 51.6 % dinilai dengan harga diri tinggi, dari ketiga komponen harga diri hanya komponen perasaan mampu yang dinilai rendah sehingga dapat disimpulkan pasien thalasemia remaja mempunyai harga diri tinggi.Hal ini perlu dipertahankan dan untuk meningkatkan komponen yang rendah, perlu adanya upaya dari petugas kesehatan untuk membantu pasien mengidentifikasi aspek positif dan kemampuan yang dimiliki.Â Kata kunci : Thalasemia, harga diri, remaja